2019
DOI: 10.3389/fphy.2019.00042
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Neutrino Signals of Low and Intermediate Energy Neutrinos on Cd Detectors

Abstract: Neutrino-nucleus reactions cross sections, obtained for neutrino energies in the range εν ≤ 100 − 120 MeV (low-and intermediate-energy range), which refer to promising neutrino detection targets of current terrestrial neutrino experiments, are presented and discussed. At first, we evaluated original cross sections for elastic scattering of neutrinos produced from various astrophysical and laboratory neutrino sources with the most abundant Cd isotopes 112 Cd, 114 Cd and 116 Cd. These isotopes constitute the mai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 97 publications
(271 reference statements)
0
2
0
Order By: Relevance
“…where the th moment is defined as (138) The authors [66] performed calculations within the current deformed shell model (DSM). The form factors of the 127 I and 133 Cs nuclei were calculated using the effective interaction [80] and the space of states of spherical orbitals , , , , and on the basis of the filled 100 Sn core.…”
Section: Ce Ns and The Nuclear Structurementioning
confidence: 99%
See 1 more Smart Citation
“…where the th moment is defined as (138) The authors [66] performed calculations within the current deformed shell model (DSM). The form factors of the 127 I and 133 Cs nuclei were calculated using the effective interaction [80] and the space of states of spherical orbitals , , , , and on the basis of the filled 100 Sn core.…”
Section: Ce Ns and The Nuclear Structurementioning
confidence: 99%
“…In addition to the already discussed COHERENT experiment, which uses beams of "accelerator" (anti)neutrinos 19 from the decay of stopped pions produced in a spallation neutron source (SNS), the experiments to be discussed below are mainly supposed to use antineutrino beams from nuclear reactors or natural neutrino sources, such and the Sun or a supernova. Modern experiments with reactor and accelerator (anti)neutrinos are reviewed, for example, in [137][138][139][140]. Interest in the CEνNS research was also demonstrated at the European Spallation Source [141].…”
Section: Some Of Ceνns Experiments and Their Capabilitiesmentioning
confidence: 99%